Comparative study suggests greater care necessary in selecting absorbable sutures in surgical closings - Editorial Staff, Editorial Staff (Operating Room Nurses Association of Canada Journal, 1987)
The results of a new comparative study of sutures conducted at the University of Western Ontario's orthopaedic research laboratories early last Spring, suggest that surgeons have made mistakes in selecting sutures that don't last long enough. Greater care should therefore be given to the choice of absorbable sutures, especially those selected for organs within the body, or for those structures that are not well vascularized.